Extraction and characterization of potential biodegradable materials based on Dioscorea hispida tubers - Kamaruddin, Zatil Hazrati; Salit, Mohd Sapuan; Mohamed Yusoff, Mohd Zuhri; Jumaidin, Ridhwan (Multidisciplinary Digital Publishing Institute, 2021)
This study was driven by the stringent environmental legislation concerning the consumption and utilization of eco-friendly materials. Within this context, this paper aimed to examine the characteristics of starch and fibres from the Dioscorea hispida tuber plant to explore their potential as renewable materials. The extraction of the Dioscorea hispida starch and Dioscorea hispida fibres was carried out and the chemical composition, physical, thermal, morphological properties, and crystallinity were studied. The chemical composition investigations revealed that the Dioscorea hispida starch (DHS) has a low moisture t (9.45%) and starch content (37.62%) compared to cassava, corn, sugar palm, and arrowroot starches. Meanwhile, the Dioscorea hispida fibres (DHF) are significantly low in hemicellulose (4.36%), cellulose (5.63%), and lignin (2.79%) compared to cassava, corn hull and sugar palm. In this investigation the chemical, physical, morphological and thermal properties of the Dioscorea hispida fibre and Dioscorea hispida starch were examined by chemical composition investigation, scanning electron microscopy (SEM), particle size distribution, thermogravimetric analysis (TGA), X-ray powder diffraction (XRD), and Fourier transform infrared (FTIR), respectively. It was found that Dioscorea hispida waste is promising alternative biomass and sustainable material with excellent potential as a renewable filler material for food packaging applications.